(untitled) - Haikonen, Pentti O. (Chichester, England, 2007)
Robot Brains expertly outlines a complete system approach to cognitive machines, offering practical design guidelines for the creation of non-numeric autonomous creative machines. It details topics such as component parts and realization principles, so that different pieces may be implemented in hardware or software. Real-world examples for designers and researchers are provided, including circuit and systems examples that few books on this topic give
Keywords: Robotics,Conscious automata,Khoa học nghiên cứu người máy,Trí tuệ tự động